Emerging antifungal treatment failure of dermatophytosis in Europe: take care or it may become endemic. (22nd April 2021) - Saunte, D.M.L.; Pereiro‐Ferreirós, M.; Rodríguez‐Cerdeira, C.; Sergeev, A.Y.; Arabatzis, M.; Prohić, A.; Piraccini, B.M.; Lecerf, P.; Nenoff, P.; Kotrekhova, L.P.; Bosshard, P.P.; Padovese, V.; et al.
Abstract: Background: Dermatophytosis is a world‐wide distributed common infection. Antifungal drug resistance in dermatophytosis used to be rare, but unfortunately the current Indian epidemic of atypical widespread recalcitrant and terbinafine‐resistant dermatophytosis is spreading and has sporadically been reported in Europe. Objectives: To explore the occurrence of clinical and mycological proven antifungal drug resistance in dermatophytes in Europe. Methods: A standardized questionnaire was distributed through the EADV Task Force of Mycology network to dermatologists in Europe. Results: Representatives from 20 countries completed the questionnaires of which 17 (85 %) had observed clinical and/or mycological confirmed antifungal resistance, two countries published cases of antifungal resistance and one country had no known cases. Conclusions: This pilot study confirms that both clinical and mycological antifungal resistance exist in Europe.